Detecting LFM Parameters in Joint Communications and Radar Frequency Bands - Zhang, Kaiyu (Cranfield University, 2022)
As the traditional radar waveform, linear frequency modulation (LFM) is widely used in military applications to detect targets. Recently, civilian applications such as internet of vehicle and unmanned aerial vehicle also apply LFM waveform to sense the nearby surroundings information. However, this complicated environment usually contain other waveforms, which may adversely influence LFM signal. Thus, there has been increasing interest in using the same radio spectrum to enable the radar and communication signals to coexist. In this poster, we select the orthogonal frequency division multiplexing (OFDM) signal as the communication waveform and discuss how to detect LFM parameters under communication and radar spectrum sharing scenarios. Firstly, the traditional method, the discrete chirp Fourier transform (DCFT), is applied in this scenario to estimated LFM parameters. Secondly, the alternative approach, the Hough transform, is proposed by considering the intrinsic feature of OFDM receivers. Through simulations, we demonstrate the DCFT method and the use of the Hough transform to confirm that these can be identified to a high degree of accuracy.
Keywords: Linear frequency modulation'; 'Discrete Chirp Fourier Transform'; 'Radar and communication system'; 'DSDS21'; 'DSDS21 Poster'; 'Signal Processing'